DEVELOPING SPEAKING MATERIAL FOR TEACHING SPEAKING BASED ON COMMUNICATIVE LANGUAGE TEACHING FOR SECOND SEMESTER STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM MUHAMMADIYAH UNIVERSITY OF METRO - Fitri Palupi Kusumawati; Ratna Puspita Sari (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2019)
This Research and Development (R&D) aimed to develop as a learning media using the assessment from the experts and determine the students' response to the Speaking Textbook in improving speaking ability. It was conducted using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation. The result obtained from the small group, field test and 5 phase of the ADDIE model. Assessing the reliability of the speaking module showed the following: 1) The Content expert gave percentage 83% which means developed the content gets